The probiotics for the treatment of allergic rhinitis : A systematic review of randomized controlled trials - Sardar, Dipankar; Banerjee, Pallobe; Alam, Ashraful; Islam, Md Shahidul (Journal of BioScience and Biotechnology, 2025)
The goal of this meta-analysis is to comprehensively assess the efficacy of probiotics in treating allergic rhinitis (AR). Two researchers independently screened the literature, extracted data, and assessed the methodological quality of the included studies. Subsequently, they utilized RevMan 5.3 software to perform meta-analysis, aiming to observe the effects of probiotics on various parameters such as RQLQ scores, RTSS, blood eosinophil count, total and antigen specific IgE levels. The pooled risk was calculated using either the fixed- or random-effects model depending on the presence of significant heterogeneity. The meta-analysis encompassed 36 randomized controlled trials, involving a total of 7,400 patients. The results revealed that the RQLQ global scores (mean difference [MD] = -9.43; P < 0.00001), RQLQ nasal scores (MD = -1.52; P = 0.03), and RTSS nasal scores (MD = -1.96; P = 0.02) showed significant enhancements. However, there were no significant differences observed in blood eosinophil count (MD = -0.09; P = 0.82), RQLQ eye scores (MD = -1.45; P = 0.07), RTSS global scores (MD = -2.24; P = 0.26), RTSS eye scores (MD = -0.39; P = 0.31), total serum IgE levels (MD = -0.04; P = 0.7), or antigen-specific serum IgE levels (MD = -0.08; P = 0.81) between the probiotic and placebo groups. Patients with AR who received probiotics saw significant improvements in their quality of life and symptoms when compared to the placebo group. This suggests a new possible application strategy for probiotics in AR.